Pengaruh Perbedaan Tingkat Konsentrasi Nutrisi Terhadap Pertumbuhan dan Hasil Beberapa Varietas Tanaman Sawi Hijau (Brassica Juncea L.) Pada Sistem Aeroponik Cerdas - Fitriani, Ayu; Kurniasih, Ratih; Azmi, Tubagus Kiki Kawakibi; Kusuma, Tubagus Maulana (Jurusan Agroekoteknologi Fakultas Pertanian Untirta, 2024)
The increase in demand for mustard greens requires an increase in production by using superior varieties and improving cultivation techniques, one of which is using an aeroponic system. Aeroponics is a hydroponic technique where the plants are suspended in the air. Aeroponic systems can now be combined with IoT (Internet of Things) devices called smart aeropoics systems. The purpose of this research is to find out the effect of different varieties of mustard greens and nutrient concentrations on the growth and yield of mustard greens with a smart aeroponics system. The research was conducted in the UG Technopark Smart Farming Greenhouse from May to July 2023 using a Randomized Complete Group Design Nested Design consisting of two factors, namely factor I (main plot) is the concentration of AB Mix nutrients consisting of two levels, namely 1000 ppm and 1500 ppm. Factor II (subplots) is the type of mustard green variety consisting of four levels, namely Shinta F1, SA 764 (Princess), Tosakan and CS1443 (Serena). The results showed that different varieties had a significant effect on the growth of mustard green plants in the parameters of plant height, number of leaves, root length and leaf area. Different nutrient concentrations significantly affect the growth and yield of mustard greens in the parameters of number of leaves, root length, crown wet weight, root wet weight, crown dry weight and root dry weight.Keywords: cultivation, internet of things, sensors, smart farming, nutrients